2020
DOI: 10.3390/ijms21228433
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of the M2 Muscarinic Receptor Agonist and Chemotherapy Affects Drug Resistance in Neuroblastoma Cells

Abstract: One of the major limits of chemotherapy is depending on the ability of the cancer cells to elude and adapt to different drugs. Recently, we demonstrated how the activation of the M2 muscarinic receptor could impair neuroblastoma cell proliferation. In the present paper, we investigate the possible effects mediated by the preferential M2 receptor agonist arecaidine propargyl ester (APE) on drug resistance in two neuroblastoma cell lines, SK-N-BE and SK-N-BE(2C), a sub-clone presenting drug resistance. In both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…These results, together with the data obtained in other tumor types (i.e., neuroblastoma, breast cancer, and urothelial cancer) [13,15,40,41], highlight the M2 muscarinic receptor as a new strategic therapeutic target in cancer therapy. Therefore, a special effort to identify new selective ligands able to bind this receptor with more efficacy and to reduce the possible side effects appears clinically relevant and may open new therapeutic perspectives for glioblastoma treatment, as well as for the treatment of other tumors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These results, together with the data obtained in other tumor types (i.e., neuroblastoma, breast cancer, and urothelial cancer) [13,15,40,41], highlight the M2 muscarinic receptor as a new strategic therapeutic target in cancer therapy. Therefore, a special effort to identify new selective ligands able to bind this receptor with more efficacy and to reduce the possible side effects appears clinically relevant and may open new therapeutic perspectives for glioblastoma treatment, as well as for the treatment of other tumors.…”
Section: Discussionsupporting
confidence: 57%
“…mAChRs are expressed in several primary and metastatic tumors, such as breast [ 7 ], ovarian [ 8 ], and lung cancers [ 9 ] and in astrocytoma and glioblastoma cells [ 10 , 11 , 12 ]. In particular, M2 mAChRs appear to be involved in tumor behavior, negatively modulating the proliferation and the migration of cancer cells [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same dose as APE, N-8-Iper not only reduced cell growth but also caused cell death [43]. Our more recent studies have shown that M2 receptor activation by APE caused a downregulation of the ATP-binding cassette (ABC) efflux pumps expression in neuroblastoma and in breast cancer [44,45]. Furthermore, co-treatment with chemotherapy drugs and M2 mAChR agonists significantly counteracts cell proliferation when compared with the single treatment [44].…”
Section: Introductionmentioning
confidence: 97%
“…Our more recent studies have shown that M2 receptor activation by APE caused a downregulation of the ATP-binding cassette (ABC) efflux pumps expression in neuroblastoma and in breast cancer [44,45]. Furthermore, co-treatment with chemotherapy drugs and M2 mAChR agonists significantly counteracts cell proliferation when compared with the single treatment [44]. Based on these results, in the present work we firstly investigated the ability of N-8-Iper to modulate cell proliferation in another GSC line (G166 cells) in order to extend the previous observation obtained in a single cell line (GB7).…”
Section: Introductionmentioning
confidence: 99%
“…However, when analyzing the function of mAChRs in tumor tissues, other authors confirmed opposite results, particularly considering the expression and function of the M2 receptor subtype. LucianĂČ et al [ 143 ], for example, established that two cell lines derived from a neuroblastoma with bad prognosis, SK-N-BE and SK-N-BE(2C), express the M2 receptor and that its activation inhibits the cell cycle. In human bladder tumors, Pacini et al [ 125 ] reported the expression of M2 receptor protein and found that its stimulation reduced cell proliferation and migration.…”
Section: Muscarinic Acetylcholine Receptorsmentioning
confidence: 99%